Content Analysis of Developed Science Textbooks (Collins) for the Tenth Grade in Jordan in View of the Constructivism Theory - Alamyreh, Mohammad Salameh (Journal of Educational and Psychological Sciences, 2021)
The study aimed to analyze the content of developed science textbooks (Collins) for the tenth grade in Jordan: Physics, Chemistry, Biology, and Geology and Environment. the study has used the analytical descriptive approach, for achieving the objective of the study the researcher has made a content analysis tool of the principles of constructivism theory that include the following five principles: Prior Knowledge, Knowledge Building, Change of Knowledge Structure, Confronting Situation, and Social Negotiation. The results that the percentage of the principles of the constructivism theory are as follows: Physics textbook (28.57%), Geology and Environment textbook (25.21%), Biology textbook (24.28%), and Chemistry textbook (21.84%). And the study recommended conducting more studies to identify the principles of the constructivism theory in textbooks and other academic grades.
Keywords: Constructivism Theory; Content Analysis; Science Textbooks; Tenth Grade